Television Talk A History of the TV Talk Show - Timberg, Bernard M. (University of Texas Press, 2021)
Flip through the channels at any hour of the day or night, and a television talk show is almost certainly on. Whether it offers late-night entertainment with David Letterman, share-your-pain empathy with Oprah Winfrey, trash talk with Jerry Springer, or intellectual give-and-take with Bill Moyers, the talk show is one of television's most popular and enduring formats, with a history as old as the medium itself. Bernard Timberg here offers a comprehensive history of the first fifty years of television talk, replete with memorable moments from a wide range of classic talk shows, as well as many of today's most popular programs. Dividing the history into five eras, he shows how the evolution of the television talk show is connected to both broad patterns in American culture and the economic, regulatory, technological, and social history of the broadcasting industry. Robert Erler's "A Guide to Television Talk" complements the text with an extensive "who's who" listing of important people and programs in the history of television talk